Building capacity through networking: Lurkers, Seekers, Leaders - Datt, Ashwini (Proceedings of the International Conference on Networked Learning, 2024)
Networks are an ally for higher educators: providing them an avenue to connect beyond the boundaries of space, time, and institutional hierarchy, to build professional capacity. This paper reports on an ethics approved mixed methods study on the value of networking to develop capacity for teaching with technologies. Data were collected via the means of anonymous online questionnaire and semi-structured interviews. There were 218 valid questionnaire responses and 31 interviews with participants from 23 countries worldwide. The value creation framework by Wenger, Trayner and deLaat (2011) was the main reference concept for data collection, analysis and reporting. The findings show that higher educators create value in networks to build capacity to teach with technologies by taking the role of Lurker, Seeker or Leader.